Technical Factors Affecting to the Dried Mango (Mangifera Indica) Leaf Tea Production - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Mango (Mangifera indica L.) was a juicy stone fruit belongs to the family of Anacardiaceae. Mango fruits were an important source of micronutrients, vitamins and other phytochemicals. Mango (Mangifera indica) leaf was used as astringent, refrigerant styptic, vulnerary and constipating. They are also useful in vitiated conditions of cough, hiccup, hyperdipsia, burning sensation, hemorrhages, haemoptysis, haemorrhoids, wounds, ulcers, diarrhoea, dysentery, pharyngopathy, scorpion string and stomachopathy. The ash of burnt leaves was useful in burns and scalds. The smoke from burning leaves was inhaled for relief of throat diseases. Tea is among the most consumed natural beverages worldwide due to its great benefits. Young leaves of mango (Mangifera indica) could be dried into herbal tea for aqueous extraction. Mangiferin is a major constituent of the leaves and stem bark of Mangifera indica. Objective of this search focused on investigating different processing aspects regarding to mango leaf tea while maintaining the most mangiferin content. Results were shown that the dried mango leaf would preserve mangiferin content by blanching the fresh mango leaf at 95oC, 4 seconds at size 2cm, then drying at 30oC by heat pump, and finally packing in PET/AL/PE bag at 4oC. By this approach, the dried mango leaf tea could be kept until 12 months without significant deterioration of mangiferin content.Keywords: Mango leaf, Mangiferin, Blanching, Drying, Packing, Tea.